Product development of fermented mushroom (Nham-Hed) with local rice varieties of three southern border provinces - Wattanayon, Wassamon; Daengrot, Charuwan; Wangsirikul, Piyaporn; Wattanayon, Rawiwan; Somwong, Tasneem (Journal of Food Technology, Siam University, 2023)
Presently, consumers are concerned about their health care and the trend of healthy food has increased the popularity. This research aims to develop the fermented mushroom with local rice varieties of three southern border provinces (Hom kradungnga rice, Lerd pla lai rice, Seebukantrang rice, and Maajanuu rice). After fermentation (27 oC) for 3 days, the fermented mushroom with each local rice was found lactic acid bacteria at 7.74-8.01 log CFU/g, pH was 4.04-4.07 and the percentage of lactic acid was 1.05-1.09. In the next step, the fermented mushroom with rice was stored at 4 oC for 4 weeks, it was found that the pH was 3.74-3.78 and the percentage of lactic acid was 1.34-1.37. The result of colour properties provided the fermented mushroom with Lerd pla lai rice was the lightest while Hom kradungnga rice product had the highest redness. And Lerd pla lai and Maajanuu rice products had the higher yellowness than the Hom kradungnga and Seebukantrang rice products. The phenolic compounds and antioxidant activity were studied in this work. The measurements show the phenolic compounds and antioxidant activity of the fermented mushroom with Hom kradungnga and Lerd pla lai rice were higher than the fermented mushroom with Seebukantrang and Maajanuu rice. The sensory acceptance score was also evaluated. The score of each product was not significantly different, however the score decreased in the fourth week because of the increasing of the sourness of all products.